Blood pressure variability and leukoaraiosis in acute ischemic stroke. Issue 5 (July 2018) - Dickie, David A; Aribisala, Benjamin; Mair, Grant; Berge, Eivind; Lindley, Richard I; Sandercock, Peter; von Kummer, Rudiger; von Heijne, Anders; Peeters, Andre; Cala, Lesley; Farrall, Andrew; Morris, Zoe; et al.
Higher blood pressure, blood pressure variability, and leukoaraiosis are risk factors for early adverse events and poor functional outcome after ischemic stroke, but prior studies differed on whether leukoaraiosis was associated with blood pressure variability, including in ischemic stroke. In the Third International Stroke Trial, blood pressure was measured in the acute phase of ischemic stroke immediately prior to randomization, and at 0.5, 1, and 24 h after randomization. Masked neuroradiologists rated index infarct, leukoaraiosis, and atrophy on CT using validated methods. We characterized blood pressure variation by coefficient of variance and three other standard methods. We measured associations between blood pressure, blood pressure variability, and leukoaraiosis using generalized estimating equations, adjusting for age, and a number of covariates related to treatment and stroke type/severity. Among 3017 patients, mean (±SD) systolic and diastolic blood pressure decreased from 155(±24)/82(±15) mmHg pre-randomization to 146(±23)/78(±14) mmHg 24 h later ( P < 0.005). Mean within-subject coefficient of variance was 0.09 ± 0.05 for systolic and 0.11 ± 0.06 for diastolic blood pressure. Patients with most leukoaraiosis were older and had higher blood pressure than those with least ( P < 0.0001). Although statistically significant in simple pairwise comparisons, no measures of blood pressure variability were associated with leukoaraiosis when adjusting for confounding variables ( P > 0.05), e.g. age. Our results suggest that blood pressure variability is not a potential mechanism to explain the association between leukoaraiosis and poor outcome after acute stroke.